Shifting From Real Estate to Non-Real Estate Lending Activity: Evidence on the Risk and Return Profiles of Thrift Institutions (International Journal of Banking and Finance, 2003)
In this paper we study the important period where many thrifts shifted from traditional mortgage products into consumer loan products. Specifically, we examine the impact of this move toward consumer banking on the risk and return profiles of thrift institutions. One reason given for this shift was the shrinldng margins associated with the traditional mortgage lending business of the thrift industry. Other reasons are increased competition from pure-play competitors and the increased merger activity among commercial banks enabling thrifts to market themselves as consumer banks. All of these reasons help to explain why the traditional thrift model became less viable. What strategic changes are necessary for thrift institutions to survive and compete effectively in the todayâ€™s financial environment? Thrifts may choose to rearrange their product mix, expand their investment portfolio, manage the enterprise more efficiently, or some combination of these, strategies. One strategy chosen by certain thrifts has been to shift from the traditional model of a mortgage-oriented lender to that of a consumer bank. Using market data from the first quarter of 1985 to the fourth quarter of 1992, we examine whether thrift organizations that followed this consumer banking strategy increased or decreased their overall exposure to risk. Employing the volatility of equity returns as our measure of total thrift risk, we find that thrifts that specialized in consumer lending exhibited lower risk while maintaining similar common stock returns, relative to thrifts that did not specialize in consumer lending. This suggests that thrifts employing a strategy of significantly diversifying their asset portfolios by specializing in consumer lending were rewarded by the equity market. Conversely, thrifts that invested only a small proportion of their assets in the consumer banking strategy did not receive a similar reward from the equity market for diversifying into consumer banking.